2013
DOI: 10.1007/s10151-013-1022-y
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation in the treatment of severe faecal incontinence: long-term clinical, manometric and quality of life results

Abstract: Analysis of our long-term results confirms the safety and effectiveness of SNS in the management of patients with FI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…Excluding patients with immediate lack of efficacy, early rates of successful permanent implantation in the present series (PP, 87·1 per cent; ITT, 58·2 per cent) were slightly below most reported values. The reasons for this are unclear.…”
Section: Discussioncontrasting
confidence: 76%
“…Excluding patients with immediate lack of efficacy, early rates of successful permanent implantation in the present series (PP, 87·1 per cent; ITT, 58·2 per cent) were slightly below most reported values. The reasons for this are unclear.…”
Section: Discussioncontrasting
confidence: 76%
“…the frequency of surgical complications (tables 3 and 4 and appendix table 5) ranged from 0% to 32% in radiofrequency anal sphincter remodeling, [48][49][50][51][52][53] 21% to 74% in aCe, 54-57 5% to 27% with sphincteroplasty, 13,37,42-45,58-66 2% to 93% with sns, 13,29,30,36,41,47,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] 8% to 64% with other surgeries, 33,38,39,86 and 22% to 100% with sphincter replacement. 13,32,46,[87][88][89][90][91][92][93][94][95][96][97][98]…”
Section: Other Surgeries and Mixed Treatment Comparisonsmentioning
confidence: 99%
“…table 4 and appendix table 5), and 3% to 24%41,47,[67][68][69]71,72,[74][75][76][77][78][79][80][81]85 of patients had the device explanted. aCe, sphincter repair, and sphincter replacement had more severe complications (wound infection, stenosis, bowel obstruction, sepsis, and fistula; appendix table 5).…”
mentioning
confidence: 99%
“…Multiple studies over the last year have reported long-term outcomes, demonstrating that the majority of patients treated with SNS experience lasting improvements in incontinence and QOL with minimal complications at mean follow ups ranging from 3-9 years [22][23][24]. Multiple studies over the last year have reported long-term outcomes, demonstrating that the majority of patients treated with SNS experience lasting improvements in incontinence and QOL with minimal complications at mean follow ups ranging from 3-9 years [22][23][24].…”
Section: Nerve Stimulation Techniquesmentioning
confidence: 99%